Using Sesame Meal Protein Hydrolysates With Pepsin As An Alternative Nitrogen Source In Some Culture Media For Growing Microorganisms (International Journal of Environmental Sciences, 2025)
The study aimed to use defatted sesame meal as a rich protein source, exploiting its high protein content, extracting and enzymatically analyzing it, and using the resulting protein hydrolysates as an alternative to expensive nitrogen sources in some culture media for growing specific microorganisms. The extraction process was carried out using 70% ethanol, and the amino acids were identified using HPLC. The results showed that the highest amino acid percentages were glutamic acid (14.15%), arginine (11.25%), and aspartic acid (6.15%), while essential acids such as leucine (5.62%), lysine (2.68%), and methionine (2.36%) recorded lower percentages. Enzymatic hydrolysis of the protein was performed using pepsin, with the highest degree of hydrolysis reaching 37% after 180 minutes. The highest solubility was recorded at pH = 11, while the highest water holding capacity reached 2.9 g/g at pH = 7.The protein hydrolysates were used in the preparation of Nutrient agar and MacConky agar media after replacing peptone as a nitrogen source with these hydrolysates. The numbers of Bacillus subtilis and Staphylococcus aureus reached (167, 150, 158) and (205, 185, 190) colony forming units (CFU) × 10⁵ CFU, when using commercial and modified media after 180 and 240 mins, respectively. However, the numbers of Escherichia coli and Salmonella typhi reached (175, 150, 162) and (155, 132, 143) × 10⁵ CFU. The efficiency of these decomposers in stimulating the growth of Aspergillus niger and Aspergillus flavus was evaluated using commercial and modified Sabouraud Dextrose Agar media. The growth diameters of A. niger were recorded at (535, 525, 530) mm, and those of A. flavus at (450, 430, 440) mm. The results indicated the effectiveness of the protein hydrolysates produced from sesame meal in supporting the growth of microorganisms, confirming their potential as an alternative and effective nitrogen source in the preparation of culture media.